AN ANALYSIS OF MERCURY (HG) LEVELS IN RIVER WATER AROUND THE GOLD MINING AREA IN BANYUWANGI REGENCY - Ani Qomariyah; Sinta Nuriyah Putri Ayu; Adhinda Fisabilla; Adisa Oktafiani; Okta Nata Kusuma; Brunika Mega Handayani; Deo Fernanda Wijaya (International Journal of Medicine and Health, 2022)
Mercury (Hg) is a metal that is commonly found in water and has toxic properties, so it is very dangerous for human health and the environment. Mercury in the environment can come from gold mining activities such as in Pesanggaran Village, Banyuwangi. Based on information from the surrounding community, the waste disposal flowed into the river and it was feared to affect the quality of river water in this area. This study aimed to analyze the mercury level in the river water using the UV-Visible Spectrophotometer method, where river water samples were taken from the upstream, middle, and downstream parts. Determination of mercury levels was carried out at the STIKES Banyuwangi Laboratory. The results showed that the Hg content in the river water around the gold mining area of Pesanggaran Village, Banyuwangi ranged from 0.031 to 0.033 mg/L. The Hg level of river water in this area was above the threshold and it was not recommended to use as drinking, bathing, cooking or washing. However, it is necessary to analyze Hg levels using other methods, such as the AAS (Atomic Absorption Spectroscopy) method which is more expensive but more accurate results will be obtained.